The Emergence of Fintech in Higher Education Curriculum - Yamato Shino; Chandra Lukita; Kim Beom Rii; Efa Ayu Nabila (Pandawan Sejahtera Indonesia, 2022)
The digital revolution in economic sectors such as e-commerce and financial technology has affected various industries, one of which is the financial industry in various parts of the world. Conventional finance in the industrial era 4.0 is being challenged by the existence of fintech as an innovation in various financial sectors. Employment opportunities are wider with fintech than conventional ones. However, this digital finance requires human resources to support it. The university acts as a competent and competitive human resource maker in the financial sector by incorporating fintech into its curriculum. Sharia fintech also needs to be applied to the curriculum of a university. Islamic universities are also able to implement fintech in their curriculum. The method used in this study uses a literature review method with evaluation results from the application of fintech at the University. The original proposition in this study incorporates hypothetical commitments in regards to monetary innovation. Utilizing the methodical writing audit approach of Kitchenham, notwithstanding topical investigation, meta-examination and perception to approve the nature of writing and investigation, the consequences of this study give a hypothetical premise fintech research from a data frameworks point of view, including the plan of fintech innovation ideas and their turn of events.